Correlates of Depression Among Elderly Population Residing in a Community in Eastern Nepal - Sharma, Khem Raj; Yadav, Birendra Kumar; Battachan, Meika (Birat Journal of Health Sciences, 2018)
Introduction: With an increase in life expectancy, demographic transition has led to sharp rise in number of elderly population. The elderly population growth rate per year has always been more than the total population growth rate, signifying the start of the ageing dynamics in Nepal. Mental health is a neglected health problem of the elderly in Nepal, with depression topping the list. This needs to be addressed in the national programs for the elderly to bring about an overall improvement in their health status. Objectives: This study was conducted with objectives to identify the prevalence of depression and factors associated with it in an urban municipality of eastern Nepal. Methodology: A community based cross-sectional study was conducted using the Geriatric Depression Scale- Short Form (GDS-SF) with 15 questions to screen for depression with a cutoff of 4/5. Door to door visit was done for data collection and face to face interviews were conducted. Pearson's Chi-square was used and Odds Ratio (OR) with confidence limits was calculated for inferential statistics. Logistic regression analysis was performed for all independent variables significantly associated in the bivariate analysis. Results: Among the 353 study subjects interviewed, depression was identified in 65.2% by GDS-SF. Regression Model showed that age more than 70 years, being in the lower class of Kuppuswamy Socioeconomic scale and elderly who were not satisfied with the respect given by their community had more odds of being depressed. Conclusion: Prevalence of depression among elderly was found to be very high in this study which was significantly associated with older age, low socio-economic status and perceived lack of respect from the community. BJHS 2018;3(1)5 : 325-330